Reliability and validity of a revised version of the General Nutrition Knowledge Questionnaire - Kliemann, N; Wardle, J; Johnson, F; Croker, H (European journal of clinical nutrition, 2016)
Background/Objectives: The General Nutrition Knowledge Questionnaire (GNKQ) was developed in the 1990s and has been widely used. Since then advances in understanding of associations between diet and disease have led to changes in dietary recommendations. This study reports the validity and reliability of an updated version of the GNKQ, bringing it into line with current nutritional advice. Methods/Subjects: Following a review of current recommendations, the revised version of the GNKQ (GNKQ-R) was created, consisting of 88 items and four sections. Reliability and validity of the GNKQ-R were determined in four validation studies: (1) reliability was examined using an online sample ( n =266), (2) construct validity was assessed with 96 Dietetics students and 89 english students using the ‘known-groups’ method, (3) associations between nutrition knowledge and socio-demographic characteristics were examined using the previously described samples and (4) sensitivity to change was tested by measuring GNKQ-R scores pre- and post-exposure to online nutrition information in written ( n =65) and video ( n =41) formats. Results: The reliability was >0.7 in all sections. Dietetics students scored significantly higher than english students. As predicted, GNKQ-R scores were significantly higher among females vs males, people with a degree vs without, and people with very good vs poor or good health status. They were lower in those older than 50 years vs younger adults. GNKQ-R scores were significantly greater after the nutrition interventions in both written and video formats. Conclusions: The GNKQ-R is a valid measure of nutrition knowledge that is consistent, reliable and sensitive to change.